Rezension von: Thalmann, Rita; Feinermann, Emmanuel, Die Kristallnacht - Bienert, Hans-Dieter (Württembergisch Franken, 1989)
Rita Thalmann; Emmanuel Feinermann: Die Kristallnacht. Frankfurt am Main: Athenäum 1988. 235 S.